Defect State Analysis in Ion‐Irradiated Amorphous‐Silicon Heterojunctions by HAXPES. Issue 5 (29th January 2019) - Lee, Min‐I; Defresne, Alice; Plantevin, Olivier; Ceolin, Denis; Rueff, Jean‐Pascal; Roca i Cabarrocas, Pere; Tejeda, Antonio
Abstract : The efficiency in HIT (heterojunction with intrinsic thin film) solar cells strongly depends on the passivation of dangling bonds at the a‐Si:H/c‐Si interface by hydrogen, introduced during the plasma‐enhanced CVD process. Herein, controlled defects that are introduced by Ar ion irradiation have been studied. It has been observed by hard X‐ray photoemission spectroscopy (HAXPES) that during Ar ion implantation, Si–H bonds in the a‐Si:H layer are broken and become dangling bonds. The number of dangling bonds in the a‐Si:H layer has been quantified, and the electronic states associated to them have been identified, which explains previously observed photoluminescence transitions. Abstract : The efficiency in HIT (heterojunction with intrinsic thin film) solar cells depends on the passivation of dangling bonds at the a‐Si:H/c‐Si interface by hydrogen. Controlled defects introduced by irradiation are studied. Hard X‐ray photoemission spectroscopy (HAXPES) shows that irradiation breaks Si–H bonds giving rise to dangling bonds. The electronic states associated to them are identified, explaining previously observed photoluminescence transitions.